Performance Analysis and Evaluation of a Multi-Hop Routing Protocol for Wireless Multimedia Sensor Networks - Saleem, Madyen M.; Alabady, Salah Abdulghani (ECTI Transactions on Electrical Engineering, Electronics, and Communications, 2022)
Researchers in wireless multimedia sensor networks (WMSNs) are constantly interested in designing and developing energy-efficient routing protocols. Numerous clustering routing protocols have been developed in recent years to overcome the limitation of consuming less energy and prolong the lifetime of sensor nodes in homogeneous and heterogeneous WMSNs. Existing approaches depend on single-hope communication, in which sensor nodes consume more energy and die faster. Inter-communication nodes can play an important role in reducing energy by transmitting data in a multi-hope fashion to the sink. An energy-efficient multi-path clustering with load balancing routing protocol for wireless multimedia sensor networks (EEMCL) is proposed in this study. In this protocol, the main cluster heads (MCHs) are preselected in each network cluster and filled with more energy than normal sensor nodes. The two secondary cluster heads (SCHs) with the highest energy nodes will be selected by the main cluster head algorithm. Moreover, inter-cluster multi-hop routing with the help of MCHs can enhance the network lifetime when the sink is located at the corner of the sensing field. The simulation results verify that the proposed multi-hop technique provides better performance than existing LEACH, LEACH-C, SEEN, and IEE-LEACH routing protocols in scenario 1 and when compared with CPMA in scenario 2. The last node dead (LND) for the proposed protocol is at round 5721, 2225 for LEACH, 2300 for LEACH-C, 2900 for SEEN, and 3160 for IEE−LEACH in scenario 1, while in scenario 2, the LND for the proposed protocol is at round 3820 and 435 for the CPMA routing protocol.